Killing in defence of property under Brunei penal laws: a comparative analysis - Masum, Ahmad; Ahmad, Muhamad Hassan; Ramlee, Nurzakiah (Serials Publications Pvt. Ltd., 2021)
Killing in defence of property is a legal issue as well as a practical problem. As the general public do not fully grasp the law of private defence, they are likely to have impromptu responses in situations where they are unlawfully attacked and their possessions unlawfully appropriated. Killing in defence of property is recognised both under the Brunei Penal Code (Cap.22) and the Brunei Shariah Penal Code Order, 2013. This is by virtue of section 103 and section 32 respectively. The paper aims to comparatively analyse the two sections in terms of the operation of the right of private defence of property justifying the killing of the aggressor. The paper concludes that the issue of whether the law should ever justify the killing in defence of property is a question which cannot be easily answered and recommends that the right to kill in defence of property must be carefully circumscribed.